2010
DOI: 10.2174/1874331501004010135
|View full text |Cite
|
Sign up to set email alerts
|

Selected Process Alternatives for Biomass Refining: A Review

Abstract: Abstract:The role of biorefineries in the production of energy and chemicals from biomass of lignocellulosic nature is reviewed. Special attention is devoted to biorefinery schemes dealing with the fractionation of lignocellulosic raw materials by chemical treatments. The potential of hydrothermal treatments as the first stage of future biorefineries is discussed. Special attention is devoted to the low-volume, high-added value products that can be solubilized by this type of technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…1 shows the scheme of a biorefinery using hydrothermal processing. This process has been mainly used as a pretreatment for bioethanol production; in recent researches, the use of a sequential process has been applied as an alternative of papermaking production, also as a technology for converting agro-food by-products into useful food ingredients [12,[65][66][67][68][69][70][71].…”
Section: Hydrothermal Processing Of Lignocellulosic Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 shows the scheme of a biorefinery using hydrothermal processing. This process has been mainly used as a pretreatment for bioethanol production; in recent researches, the use of a sequential process has been applied as an alternative of papermaking production, also as a technology for converting agro-food by-products into useful food ingredients [12,[65][66][67][68][69][70][71].…”
Section: Hydrothermal Processing Of Lignocellulosic Materialsmentioning
confidence: 99%
“…During the hydrothermal processing lignin and lignin-hemicellulose linkages can undergo degradation, partial depolymerization and profound re-localization. Moreover, the fraction of solubilized lignin depends on the operation conditions (severity of reactions conditions) and on the raw material (LCMs) [28,66,127]. Lora and Wyman (1978) and Bobleter and Concin (1979) cited by Garrote et al [28] and Zhang et al [187] suggested a two-phase mechanism for lignin reaction: (1) a very fast reaction where lignin fragments with low molecular weight and high reactivity are solubilized by breaking lignin-carbohydrate bonds into soluble fragments; (2) a slower reaction where the soluble fragments react with one another by recondensantion and lignin repolimerization, which also occurs in the presence of the organic acids liberated in the hydrothermal processing.…”
Section: Effect Of Hydrothermal Processing On Ligninmentioning
confidence: 99%
See 2 more Smart Citations
“…While decreasing crude-oil reserves, enhanced demand for fuels worldwide, increased climate concerns about the use of fossil-based energy carriers, and political commitment, the focus has recently turned to develop the utilization of renewable energy resources [2]. Gullón et al [3] described the variety of problems on present social, economic and technological situation, which including: the fear for a shortening of the supplies of basic resources, as the population growth; the increasing per capita demands of the developing economies for goods and energy, derived from the increasing purchase power of the population; environmental challenges, especially those related to effects of greenhouse gas emissions (emphasis on CO2) on the global climate; the national security issues surrounding reliance on imported oil [4].…”
Section: Introductionmentioning
confidence: 99%